2017
DOI: 10.1590/s1678-9946201759036
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoid-like cutaneous lesions in chronic adult paracoccidioidomycosis: report of two cases

Abstract: This study reports two cases of chronic paracoccidioidomycosis with sarcoid-like cutaneous lesions. The patients began the treatment in 2013 at Hospital Universitário Clementino Fraga Filho (HUCFF) of the Universidade Federal do Rio de Janeiro (UFRJ). The first case (mild form) was treated with trimethoprim-sulfamethoxazole (8 mg /kg per day, orally) for three months and, then, with half the dose for nine months; the second (moderate form), with itraconazole (200 mg per day, orally) for 12 months. We point out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Studies have shown that the infiltrative pattern corresponds to up to 26.6% of the observed skin lesions, including sarcoid-type lesions 9 . This clinical presentation is rare and typically manifests as well-defined infiltrated or lichenoid lesions, usually at the cephalic pole 1 . These patients exhibit a predominant T helper 1 (Th1) immune response, which results in compact granulomas with scarce or undetectable fungi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the infiltrative pattern corresponds to up to 26.6% of the observed skin lesions, including sarcoid-type lesions 9 . This clinical presentation is rare and typically manifests as well-defined infiltrated or lichenoid lesions, usually at the cephalic pole 1 . These patients exhibit a predominant T helper 1 (Th1) immune response, which results in compact granulomas with scarce or undetectable fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Paracoccidioidomycosis (PCM) is a systemic mycosis caused by thermally dimorphic fungi of the genus Paracoccidioides 1 . Typically, most patients have a history of rural living and are frequently associated with smoking and alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a variant of cutaneous PCM that manifests itself in the skin with infiltration, similar to sarcoidosis, called sarcoid or sarcoidosis-like form, being considered a subtype of PCM-disease [1] , [3] . This form is rare and histologically characterized by the presence of tuberculoid granulomas and scarcity of fungal structures [1] , [2] , [3] , [4] , [5] , [8] . This is due to the host's immune response, because when the individual presents a competent immune response to P. brasiliensis , a stimulus is given to generate the T helper 1 (Th1) lymphocytes response.…”
Section: Discussionmentioning
confidence: 99%
“…quently, this manifestation is reported as being caused by misdiagnosis, justifying the initial diagnosis of sarcoidosis in this case. [4][5][6] The sarcoid pattern of PCM can be determined by a specific immune response, which leads to a certain balance between agent and host and generates paucifungal histological exams, hindering the correct diagnosis. 7 In this case, treatment with prednisone probably altered such balance, favoring an immunosuppression that allowed lesions to evolve into ulcerated forms, which are more typical of the disease and contain an increased amount of yeasts, facilitating the correct diagnosis.…”
mentioning
confidence: 99%